Wavelet-Based Progressive Image Transmission System For Telemedicine Application - Kadim, Zulaikha (2005)
Telemedicine has been defined as the use of telecommunications to provide medical information and services. In this study, we are proposing a wavelet-based progressive transmission algorithm for medical images, which will fulfill certain criteria of medical image transmission. To accomplish the target, we have studied several potential integer wavelet transforms and wavelet-based image coders that best work for the system.